Symptoms associated with common mental disorders in the university context (Research, Society and Development, 2020)
Objective: was to identify symptoms associated with minor psychotic disorders in university students from a public Higher Education Institution (HEI) in the inland of Ceará. Methodology: It is a descriptive, cross-sectional, quantitative approach, developed from April to May 2019 with 75 undergraduate students using the adaptation of the questionnaire for the identification of common mental disorders (CMD). Results: The prevalence of CMD in the population was (49%), between 18 and 23 years old (84%), with somatic symptoms in (32%) of the population and decrease of energy (29%) besides depression and/or anxious mood with prevalence, in the first semesters of graduation (39%). Conclusion: CMDs are an important problem for young people in higher education. The need for interventions in the academic community by management, employees, professionals and students with a focus on empowerment and treatment of the underlying causes of disorders is highlighted.